2014
DOI: 10.1088/0004-637x/786/2/137
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Observations of the Shock Wave Behavior for Sunspot Oscillations With the Interface Region Imaging Spectrograph

Abstract: We present first results of sunspot oscillations from observations by the Interface Region Imaging Spectrograph (IRIS). The strongly nonlinear oscillation is identified in both the slit-jaw images and the spectra of several emission lines formed in the transition region and chromosphere. We first apply a single Gaussian fit to the profiles of the Mg ii 2796.35Å, C ii 1335.71Å and Si iv 1393.76Å lines in the sunspot. The intensity change is ∼30%. The Doppler shift oscillation reveals a sawtooth pattern with an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 54 publications
23
102
0
Order By: Relevance
“…Figure 10, extracted from Brynildsen et al (1999a), shows that the intensity-velocity time lags are very small, characteristic for the vertical wave propagation. With a better temporal resolution, Tian et al (2014) find that the intensity enhancement of the Mg ii 2796Å line formed in the high chromosphere occurs slightly before the maximum blueshift is reached. A similar behavior was also found for the Ca ii H and K lines by Rouppe van der Voort et al (2003).…”
Section: Oscillations In the Transition Region And Coronamentioning
confidence: 92%
See 2 more Smart Citations
“…Figure 10, extracted from Brynildsen et al (1999a), shows that the intensity-velocity time lags are very small, characteristic for the vertical wave propagation. With a better temporal resolution, Tian et al (2014) find that the intensity enhancement of the Mg ii 2796Å line formed in the high chromosphere occurs slightly before the maximum blueshift is reached. A similar behavior was also found for the Ca ii H and K lines by Rouppe van der Voort et al (2003).…”
Section: Oscillations In the Transition Region And Coronamentioning
confidence: 92%
“…From these parameters, some authors have suggested that the three-minute chromospheric oscillations above sunspot umbrae are standing acoustic waves , while others found them to be propagating waves able to reach the upper layers of the solar atmosphere Banerjee et al, 2002;O'Shea et al, 2002;Brynildsen et al, 2003Brynildsen et al, , 2004Kobanov and Makarchik, 2004). The typical sawtooth pattern of propagating shock wave fronts has been made patent in many observations using different chromospheric and transition region lines (see, e.g., Rouppe van der Voort et al, 2003;Centeno et al, 2006;Tian et al, 2014). Examples of such profiles are given in Figures 3 and 5 as derived from the observations in He i and Ca ii H lines in the above mentioned works.…”
Section: Propagation From the Photosphere To The Chromospherementioning
confidence: 99%
See 1 more Smart Citation
“…The EUV observations from the Atmospheric Imaging Assembly (AIA; Lemen et al 2012) onboard the Solar Dynamics Observatory (SDO; Pesnell et al 2012) were used to compare with the IRIS data. Cross-correlation between the AIA 1600 Å image and the IRIS SJI 1400 Å image was used for the coalignment (Tian et al 2014b). The full-disk line-ofsight magnetograms from the Helioseismic and Magnetic Imager (HMI; Scherrer et al 2012) were also applied to analyze the magnetic structures at the BPs.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…Figure 4 shows the effect of de-spiking. In addition, small spectral shifts caused by thermal drifts and the spacecraft orbital velocity were corrected with the routine iris_orbitvar_corr_12.pro (McIntosh et al 2013;Tian et al 2014;Cheng et al 2015) in the SSW package.…”
Section: Iris Observationsmentioning
confidence: 99%